2023
DOI: 10.1590/s1677-5538.ibju.2022.9980
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the lower hypogastric plexus applied to endometriosis: a narrative review

Abstract: Objective The objective of the present study is to evaluate the anatomy of the inferior hypogastric plexus, correlating it with urological pathologies, imaging exams and surgeries of the female pelvis, especially for treatment of endometriosis. Material and Methods We carried out a review about the anatomy of the inferior hypogastric plexus in the female pelvis. We analyzed papers published in the past 20 years in the databases of Pubmed, Embase and Scielo, and we inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Dr. Ribeiro-Julio and collegues from Brazil, presented in page 299 ( 2 ) a important review about the anatomy of the lower hypogastric plexus applied to endometriosis and concluded that the Accurate knowledge of the innervation of the female pelvis is of fundamental importance for prevention of possible injuries and voiding dysfunctions as well as the evacuation mechanism in the postoperative period. Imaging exams such as nuclear magnetic resonance are interesting tools for more accurate visualization of the distribution of the hypogastric plexus in the female pelvis.…”
mentioning
confidence: 99%
“…Dr. Ribeiro-Julio and collegues from Brazil, presented in page 299 ( 2 ) a important review about the anatomy of the lower hypogastric plexus applied to endometriosis and concluded that the Accurate knowledge of the innervation of the female pelvis is of fundamental importance for prevention of possible injuries and voiding dysfunctions as well as the evacuation mechanism in the postoperative period. Imaging exams such as nuclear magnetic resonance are interesting tools for more accurate visualization of the distribution of the hypogastric plexus in the female pelvis.…”
mentioning
confidence: 99%